Correcting Abnormal Flexion-Relaxation in Chronic Lumbar Pain: Responsiveness to a New Biofeedback Training Protocol - Neblett, Randy (2010)
OBJECTIVES: Lumbar flexion-relaxation is a well-known phenomenon that can reliably be seen in normal subjects, but not in most chronic low back pain (CLBP) subjects. No previous studies have investigated any specific clinical intervention designed to correct abnormal flexion-relaxation. The objective of the current study was to evaluate the contribution of a surface EMG-assisted stretching (SEMGAS) biofeedback training protocol, within a functional restoration treatment program, on flexion range of motion (ROM) and erector spinae surface EMG (SEMG) during maximum voluntary flexion (MVF). METHODS: Lumbar flexion ROM and MVF SEMG were assessed in two groups of CLBP patients at the beginning and end of rehabilitation. One group participated in functional restoration only, while the other group participated in functional restoration plus SEMGAS biofeedback training. Both treatment groups were compared to a separate control group of normal, pain-free subjects. RESULTS: Pre-treatment ROM and MVF SEMG measures were similar in both treatment groups, but were very different than the control group. At post-treatment, the functional restoration only group remained statistically different than the control group on MVF SEMG and some ROM measures, but the SEMGAS group was statistically equivalent to the control subjects on all post-treatment measures, including the ability to demonstrate flexion-relaxation. DISCUSSION: Interdisciplinary functional restoration rehabilitation of CLBP subjects is effective for increasing ROM and other functional measures, but the addition of a SEMGAS biofeedback training protocol can result in normalization of the flexion-relaxation phenomenon, so that these subjects are comparable to a pain-free control group.